(3GdCegGJs - (3GHf YHGOs ((3MSjf CMeOjf s)
(3ChdgG (B:s
(3bGd QMeg Gddg (B( (3aUd (B) (3ai CegGJ eG jHfi Ydjg GdeQjO ai gPg GdCRefI hZjQgG hPdc CehQ (B( (3ChdgG (B) (3EdJRGe GdJbhi HJQc GdeMQeGJ hMaX GdhGLHGJ s
(3BNQgG (B:s
(3SJPcQg EPG LQHJ ZjQi hJMed cd CeQ MjGA efi JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdQSGdI ecJhHg Ydi GdMGTjIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJUha hGdBOGH GdTQYjIs